ADJEKTIVA BAHASA INDONESIA: TINJAUAN BENTUK, PERILAKU SEMANTIK, DAN PERILAKU SINTAKSIS - Tri Marliana; Nusarini Nusarini (CARAKA, 2015)
This research aims to (1) describe the adjective in terms of shape, (2) Describe the behavior in terms of semantic adjectives, (3) Describe the behavior in terms of syntactic adjectives. This study included a qualitative descriptive study. Data used in the form of a sentence containing an adjective. Sources of data obtained from the Sovereignty of the People's Newspaper, newspaper Sindo, Tabloid Cempaka and Real, as well as Indonesian Books for junior class VII. Data collection method used is a method refer to freely refer techniques and techniques involved capably record. Data analysis method used in this study is agih methods and data analysis techniques used are the direct elements, techniques vanished, and inline techniques. Results of this study are as follows. Adjective in terms of form consists of (1) basic adjectives monomorfemis and (2) the derivative adjective polimorfemis. In terms of its semantic behavior consists of adjectives standard and non-standard adjective. Adjective class consisting of (a) adjective pemeri nature, (b) adjective size, (c) the color adjective, (d) adjective time, (e) adjective distance, (f) adjective inner attitude, (g) adjective perception. No standard adjective presence in the group can not be class-level. Something is inside or outside. In terms of the behavior of syntactic adjectives in Indonesian consisting of (a) adjective attributive function, (b) serves predicative adjectives, and (c) work adverbial adjective. or description.